2021
DOI: 10.1016/j.optmat.2020.110792
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and doping dependence of fluorescence lifetime in Yb:YLF (role of impurities)

Abstract: We have investigated temperature and doping dependence of fluorescence lifetime in Yb:YLF crystals in the 78-300 K range, for samples with Yb-doping levels of 0.5%, 1 % and 25%. Radiation-trapping prolonged fluorescence lifetimes are first measured to understand the pros and cons of this inevitable process on fractional thermal load and laser gain. Later, pinhole method was used to acquire ideally trapping free fluoresce lifetimes. For the lowly Yb-doped samples, fluorescence lifetime was measured to be 1.97 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 60 publications
0
4
0
1
Order By: Relevance
“…These process is weak in Yb-systems due to the simple energy level diagram. On the other hand, the emission observed at visible wavelengths in Yb:YLF clearly shows the presence of such mechanisms [38], and change of rate of these process with output coupling might be affecting the laser performance at large output coupling values. As a side note, in our experiments, we have observed that the greenish visible emission of Yb:YLF under tight pumping shifts to blue region of spectrum while using low output coupling values, that shows the role of inversion and intracavity power levels in these dynamics.…”
Section: Continuous-wave Lasing Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These process is weak in Yb-systems due to the simple energy level diagram. On the other hand, the emission observed at visible wavelengths in Yb:YLF clearly shows the presence of such mechanisms [38], and change of rate of these process with output coupling might be affecting the laser performance at large output coupling values. As a side note, in our experiments, we have observed that the greenish visible emission of Yb:YLF under tight pumping shifts to blue region of spectrum while using low output coupling values, that shows the role of inversion and intracavity power levels in these dynamics.…”
Section: Continuous-wave Lasing Resultsmentioning
confidence: 99%
“…6, as the temperature of the Yb:YLF crystal holder is increased, the obtainable laser output power levels slowly decrease with temperature for lasing in both axes. This decrease of output power with temperature is mainly due to the decreasing emission cross section value (as the intrinsic lifetime of the Yb:YLF material is constant over a wide temperature range) [37,38]. Based on our observations, we believe that, in future studies, using higher power pump diodes, the output power levels obtainable from roomtemperature Yb:YLF lasers could be scaled to above 10 W even in simple rod geometry, and to multi-10s of W level in thin-disk geometry.…”
Section: Continuous-wave Lasing Resultsmentioning
confidence: 99%
“…The last remaining uncertainty in the application of eq then lies in the correct value of the bulk radiative rate constant Γ rad bulk . In the literature, for the bulk lifetime, a variety of values between 2.0 and 2.2 ms can be found. ,,, Furthermore, previous reports have shown that the lifetime is temperature and Yb-concentration dependent. ,,, For the purpose of this work, we have chosen to use the bulk lifetime of 5% Yb:YLF, 2.20 ms, accurately reported by Püschel et al as fixed radiative lifetime, and used this throughout the rest of this work.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Точную причину изменения времени жизни уровня 2 F 5/2 ионов Yb 3+ на данном этапе установить сложно. Указанные предполагаемые причины были описаны в работах [30][31][32].…”
Section: спектры поглощения и люминесценцииunclassified